A Development Consensus reconciling the Beijing Model and Washington Consensus: Views and Agenda - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2014)
Reconciling the two dominant development models of the Washington Consensus (WC) and Beijing Model (BM) remains a critical challenge in the literature. The challenge is even more demanding when emerging development paradigms like the Liberal Institutional Pluralism (LIP) and New Structural Economics (NSE) schools have to be integrated. While the latter has recognized both State and market failures but failed to provide a unified theory, the former has left the challenging concern of how institutional diversity matter in the development process. We synthesize perspectives from over 150 recently published papers on development and Sino-African relations in order to present the relevance of both the WC and BM in the long-term and short-run respectively. While the paper provides a unified theory by reconciling the WC and the BM to complement the NSE, it at the same time presents a case for economic rights and political rights as short-run and long-run development priorities respectively. By reconciling the WC with the BM, the study contributes at the same to macroeconomic NSE literature of unifying a development theory and to the LIP literature on institutional preferences with stages of development. Hence, the proposed reconciliation takes into account the structural and institutional realities of nations at difference stages of the process of development.
Keywords: B10; O11; O19; O55; 330; Economic thought; Development; Beijing model; Washington Consensus; Africa